The Validity of Online Assessment Instruments for Measuring Higher Order Thinking Skills of High School Students in Physics Subject - Siti Rahmah; Festiyed (Postgraduate, University of Mataram, 2025)
Assessment instruments are assessment tools consisting of tests and non-tests which guide educators in making decisions and obtaining information on students' progress or achievement of competencies. A good assessment instrument has several requirements, including being valid and reliable. Currently there are no valid and reliable assessment instruments available that can measure students' higher order thinking skills, especially in high school physics subjects. This research aims to produce a valid and reliable instrument for measuring students' higher order thinking skills physics. The instrument of this research is questions to measure higher order thinking skills in the form of essay questions. Validity analysis is carried out by proving the validity of the content and criteria. The validity analysis results were 0.44 in the valid category and the reliability results were 0.70 in the high category. The research results show that the instrument has met the appropriate and valid criteria for measuring students' higher order thinking skills.